2022
DOI: 10.3389/fsurg.2022.862948
|View full text |Cite
|
Sign up to set email alerts
|

Virtual-Augmented Reality and Life-Like Neurosurgical Simulator for Training: First Evaluation of a Hands-On Experience for Residents

Abstract: BackgroundIn the recent years, growing interest in simulation-based surgical education has led to various practical alternatives for medical training. More recently, courses based on virtual reality (VR) and three-dimensional (3D)-printed models are available. In this paper, a hybrid (virtual and physical) neurosurgical simulator has been validated, equipped with augmented reality (AR) capabilities that can be used repeatedly to increase familiarity and improve the technical skills in human brain anatomy and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 22 publications
(30 reference statements)
3
17
0
Order By: Relevance
“…Results from our study have it that it is easy to use and easy to get acquainted with, sanctioned by a 60% and 60.9% scores on our study. This is consistent with a similar study carried out using UpSurgeOn tools, where More than 89% of the residents assessed that the application and the augmented reality simulator were very helpful in improving orientation skills during neurosurgical approaches ( 34 ). Indeed, 89.3% of participants found brain and skull anatomy highly realistic during their tasks ( 34 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Results from our study have it that it is easy to use and easy to get acquainted with, sanctioned by a 60% and 60.9% scores on our study. This is consistent with a similar study carried out using UpSurgeOn tools, where More than 89% of the residents assessed that the application and the augmented reality simulator were very helpful in improving orientation skills during neurosurgical approaches ( 34 ). Indeed, 89.3% of participants found brain and skull anatomy highly realistic during their tasks ( 34 ).…”
Section: Discussionsupporting
confidence: 89%
“…Also, the organization by the available neurosurgical centers of continental annual or bi-annual neurosurgery boot camps taking into consideration regional level of excellence and geographical proximity will improve the neurosurgical know-how of undergraduate students ( 4 , 32 ). A valid strategy to improve at the same time for neurosurgery exposure and cadaver dissection which is crucial to neurosurgical training is the use of hands-on-touch non-cadaver model for neuroanatomy/neurosurgery learning such as the UpSurgeOn models ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…VR allows for the creation of realistic, interactive environments that can be used to train surgeons and other medical professionals, as well as to test new procedures and devices. Other research has shown that VR can be an effective tool for teaching surgical skills and for training healthcare professionals in laparoscopic surgery (Aoki et al, 2020; Gleason et al, 2022; Kamat et al, 2022; Mori et al, 2022; Yu et al, 2022) and neurosurgery (Petrone et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The use of neurosurgical simulators (UpSurgeOn Box and UpSurgeOn Srl) plays a pivotal role in this course: They combine virtual and physical components to provide hybrid solutions of training so that virtual reality, augmented reality, and the physical simulator are able to guide residents from exploring anatomy to reproduce surgical approaches through a semispheric support. 6…”
mentioning
confidence: 99%
“…The use of neurosurgical simulators (UpSurgeOn Box and UpSurgeOn Srl) plays a pivotal role in this course: They combine virtual and physical components to provide hybrid solutions of training so that virtual reality, augmented reality, and the physical simulator are able to guide residents from exploring anatomy to reproduce surgical approaches through a semispheric support. 6 The course is 1 year in duration and is completely managed by residents through a hierarchical structure according to years of residency and with the supervision of fully trained neurosurgeons.…”
mentioning
confidence: 99%